2016
DOI: 10.1007/s10869-016-9457-6
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Employees’ Objective Internal and External Pay Standing and Their Job Performance: A Within-Person Analysis

Abstract: Purpose Researchers have paid little attention to the relationship between employees' objective internal and external pay standing and their job performance. Moreover, few studies have considered that employees' objective pay standing is dynamic; that is, it changes over time. In this study, we analyze the relationship between changes in employees' objective internal and external pay standing and their job performance. Design/Methodology/Approach We test the hypotheses using data for players in the National Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Furthermore, lower or decreasing LMX separation within the group may be experienced by high RLMX team members as a loss of status and power, increasing the “moral license” to take days off. These arguments are consistent with recent findings by Sieweke et al (2017) showing that employees refrain from exhibiting positive behaviors when their internal pay standing decreases. Future research is needed to examine why low LMX separation influences RLMX outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, lower or decreasing LMX separation within the group may be experienced by high RLMX team members as a loss of status and power, increasing the “moral license” to take days off. These arguments are consistent with recent findings by Sieweke et al (2017) showing that employees refrain from exhibiting positive behaviors when their internal pay standing decreases. Future research is needed to examine why low LMX separation influences RLMX outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…Research studies conducted by different scholars in the last decade provide evidence of indirect but positive relationship between PS and employee task performance (ETP) (Chiang & Birtch, 2012;Gieter & Hofmans, 2015;Kappagoda et al, 2014;Ren et al, 2017;Sieweke et al, 2017), but how PS influences ETP is still vague. All these studies show that employees' perception of their PS can affect their workrelated attitudes, including job satisfaction and motivation and in turn employee in role and extra role performance.…”
Section: Introductionmentioning
confidence: 99%
“…Given that evaluators decide whether or not to support a practice depending on whether they believe that practice to be legitimate (Hoefer and Green, ; Huy et al, ; Tost, ), our insights also have important implications for the study of management and organizations in general, and particularly for research on organizational justice (e.g., Colquitt et al, ; Greenberg and Colquitt, ) and the consequences of inequality in organizations (e.g., Bloom and Michel, ; Sieweke et al, ). For instance, previous research has shown that employee reactions to different forms of inequality (e.g., pay inequality, gender inequality) depend on the extent to which such inequalities are perceived to be fair (e.g., Shore et al, ).…”
Section: Discussionmentioning
confidence: 95%